1984
DOI: 10.1084/jem.159.2.436
|View full text |Cite
|
Sign up to set email alerts
|

Thymic cytotoxic T lymphocytes are primed in vivo to minor histocompatibility antigens.

Abstract: Potent cytotoxic T lymphocyte (CTL) activity can be derived from cultures of thymocyte responders and minor H different spleen cell stimulators. As is the case of the spleen cell response previously reported, this cytotoxic activity requires in vivo priming. We performed several experiments designed to determine whether the in vivo priming effect is due to the in situ priming of the thymocyte CTL precursors, to contamination of thymus cell preparations with cells of neighboring lymph nodes, or to the appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…There Was clearly an increase in the number of cells which migrated into the thymus following antigen-specific T cell activation in the periphery, confirming the findings of earlier studies (Naparstek et al, 1982;Fink et al, 1984;Agus et al, 1991;Bell et al, 1995;Westermann et al, 1996). This increase amounted to about 16 to 20-fold 3 days after injection with peptide.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…There Was clearly an increase in the number of cells which migrated into the thymus following antigen-specific T cell activation in the periphery, confirming the findings of earlier studies (Naparstek et al, 1982;Fink et al, 1984;Agus et al, 1991;Bell et al, 1995;Westermann et al, 1996). This increase amounted to about 16 to 20-fold 3 days after injection with peptide.…”
Section: Resultssupporting
confidence: 80%
“…Previous investigations of immigration of mature T cells to the thymus were limited by the fact that activated cells were defined and purified on the basis of cell-surface marker expression (Bell et al, 1995;Westermann et al, 1996), or involved adoptive transfer of previously activated cells (Fink et al, 1984;Agus et al, 1991). Additionally, measurement of immigrating cells has frequently relied upon relatively non-quantitative radioactive, immunohistochemical or in vitro cell culture techniques (Naparstek et al, 1982;Fink et al, 1984;Westermann et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Early observations indicated that this phenomenon might be restricted to the neonatal period, a time when the periphery is lymphopenic, or to the recirculation of some activated T cells back to the adult thymus (5). Clearly, during an ongoing antiviral immune response, some degree of priming is seen among mature thymocytes (25,26). Using either parabiosis (6) or transfer of CFSE-labeled cells (27), we have previously shown that in a situation of peripheral lymphopenia, the contribution of recirculating peripheral T cells to the pool of mature "thymocytes" was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Other thymus-expressed chemokines, TARC, LARC, MDC/STCP-1, and murine TCA4, attract mature leukocytes: TARC attracts T cell lines [27]; LARC attracts resting lymphocytes [30]; MDC/STCP-1 attracts activated T cells, monocytederived dendritic cells, monocytes, and NK cells [24,25]; TCA4 attracts mature T cells and cultured mesangial cells [32]. Recirculation of mature T cells to thymus was suggested to be a negative regulation mechanism of T lymphopoiesis [37,38]. Thus, these thymus-expressed chemoattractants for mature T cells may have a role in T lymphopoiesis by regulating the trafficking of mature T cells into thymus.…”
Section: Chemokines and Trafficking Of Lymphocyte Progenitors In Primmentioning
confidence: 99%